HPV16 RNA-LPX vaccine mediates complete regression of aggressively growing HPV-positive mouse tumors and establishes protective T cell memory. (2nd September 2019) - Grunwitz, Christian; Salomon, Nadja; Vascotto, Fulvia; Selmi, Abderaouf; Bukur, Thomas; Diken, Mustafa; Kreiter, Sebastian; Türeci, Özlem; Sahin, Ugur
ABSTRACT: HPV16 infections are associated with a variety of cancers and there is compelling evidence that the transforming activity of HPV16 critically depends on the expression of the viral oncoproteins E6 and E7. Therapeutic cancer vaccines capable of generating durable and specific immunity against these HPV16 antigens hold great promise to achieve long-term disease control. Here we show in mice that HPV16 E7 RNA-LPX, an intravenously administered cancer vaccine based on immuno-pharmacologically optimized antigen-encoding mRNA, efficiently primes and expands antigen-specific effector and memory CD8 + T cells. HPV-positive TC-1 and C3 tumors of immunized mice are heavily infiltrated with activated immune cells and HPV16-specific T cells and are polarized towards a proinflammatory, cytotoxic and less immune-suppressive contexture. E7 RNA-LPX immunization mediates complete and durable remission of progressing tumors. Circulating memory T cells are highly cytotoxic and protect from tumor rechallenge. Moreover, E7 RNA-LPX immunization sensitizes anti-PD-L1 refractory tumors to checkpoint blockade. In conclusion, our data highlight the potential of HPV16 RNA-LPX for the treatment of HPV-driven cancers.